THE EFFECT OF PROFIT MANAGEMENT, WEBSITE INFORMATION DISCLOSURE AND INTERNET FINANCIAL REPORTING ON COMPANY VALUE BY MODERATION OF THE BOARD OF COMMISSIONERS - Ridwan Fauzi Ari Hamzah; Iin Rosini (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this research is to obtain empirical evidence regarding the board of commissioners moderating the influence of earnings management, website information disclosure and internet financial reporting on company value. This research used a purposive sampling method in determining the sample with 35 companies as samples and a 5 year observation period from 2018 to 2022 so that 175 observation data were obtained. Research data was obtained through the official website of the Indonesian stock exchange and the websites of each company. Data analysis uses E-Views with panel data regression analysis using the Random Effect Model. The results of the research show that earnings management does not affect company value, website information disclosure has an effect on company value, internet financial reporting has no effect on company value, the board of commissioners moderates by weakening the influence of earnings management on company value, the board of commissioners does not moderate the effect of website information disclosure on The value of the company and the board of commissioners moderates by strengthening the influence of earnings management on company value.